2014
DOI: 10.1007/s00520-014-2159-6
|View full text |Cite|
|
Sign up to set email alerts
|

Osteonecrosis of the jaw (ONJ) in renal cell cancer patients after treatment including zoledronic acid or denosumab

Abstract: Dear Editor, The paper by Henry et al. published by Supportive Care in Cancer comparing efficacy of denosumab versus zoledronic acid in patients with bone metastases of advanced solid tumours [1] comes to integrate the original reports of three pivotal large randomized phase 3 trials [2][3][4], the publication by Saad et al. about osteonecrosis of the jaw (ONJ) in those three trials [5], and the combined outcome analysis by Lipton et al. [6].Henry et al.[1] reported outcomes of the single trial conducted on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[45,64] As previously noted, [65] there were 14 cases of ONJ in the three trials out of 464 patients (3.0%) who had been treated with an antiresorptive agent (zoledronic acid or denosumab) and antiangiogenic agents versus 75 cases of ONJ cases out of 5259 patients (1.4%) receiving zoledronic acid or denosumab and no antiangiogenic agents. This, therefore, suggests a possible higher risk of ONJ from a combination of antiresorptive and antiangiogenic agents.…”
Section: Association Of Antingiogenic Drugs and Antiresorptive Agentsmentioning
confidence: 53%
See 1 more Smart Citation
“…[45,64] As previously noted, [65] there were 14 cases of ONJ in the three trials out of 464 patients (3.0%) who had been treated with an antiresorptive agent (zoledronic acid or denosumab) and antiangiogenic agents versus 75 cases of ONJ cases out of 5259 patients (1.4%) receiving zoledronic acid or denosumab and no antiangiogenic agents. This, therefore, suggests a possible higher risk of ONJ from a combination of antiresorptive and antiangiogenic agents.…”
Section: Association Of Antingiogenic Drugs and Antiresorptive Agentsmentioning
confidence: 53%
“…This 6/155 (3.9%) ONJ frequency in RCC patients is more than twice as high if compared with the entire patient population (1.6%). [65] Unfortunately, whether those six RCC patients developing ONJ had received antiangiogenic agents or which bone antiresorptive agent had been administered was not discussed in the quoted reports.…”
Section: Association Of Antingiogenic Drugs and Antiresorptive Agentsmentioning
confidence: 99%
“…54 Bozas and coworkers 58 identified 5 ONJ cases among 21 RCC patients treated with a combination of NBP and antiangiogenic drugs (23.8%), with a cumulative hazard ratio for ONJ of 5% (95% confidence interval [CI], 0%-10%) and 36% (95% CI, 23%-49%) after 12 and 24 months of zoledronate treatment, respectively. The authors' conclusion suggested a potential synergy of sunitinib and zoledronic acid in inducing ONJ.…”
Section: Discussionmentioning
confidence: 97%
“…In the author's opinion, the combination of zoledronic acid and taxanes, plus corticosteroids, may have some synergy of effect and a particularly detrimental influence on the severity of MR-ONJ. The observation of these patients represents a starting point for reflection to stimulate the attention of the community to look after the patients treated with bone targeted therapies in combination with other agents and maximize their mouth care [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%